2017
DOI: 10.1055/s-0037-1603450
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Infection in Pregnant Women and Microcephaly

Abstract: From the discovery of the Zika virus (ZIKV) in 1947 in Uganda (Africa), until its arrival in South America, it was not known that it would affect human reproductive life so severely. Today, damage to the central nervous system is known to be multiple, and microcephaly is considered the tip of the iceberg. Microcephaly actually represents the epilogue of this infection's devastating process on the central nervous system of embryos and fetuses. As a result of central nervous system aggression by the ZIKV, this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 58 publications
(107 reference statements)
2
45
0
10
Order By: Relevance
“…58 When exposed to treatment with a range of pHs, LsCTI was stable, with none of the pHs tested being able to reduce its inhibitory activity on chymotrypsin ( Figure 5C) and trypsin ( Figure 5D). Similarly, the protease inhibitor from T. dicoccoides (WeCI) was shown to be stable in a wide pH range (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) 47 but, in contrast, the BmPI from B. monosperma was shown to maintain activity only in a pH range of 5-10. 43 The stability of LsCTI after heat treatment was remarkable; the molecule was able to maintain its inhibitory activity at all temperatures tested (37-100 ∘ C) ( Figure 5E), even when heated at 100 ∘ C for 180 min (Figure 5F), for both chymotrypsin and trypsin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…58 When exposed to treatment with a range of pHs, LsCTI was stable, with none of the pHs tested being able to reduce its inhibitory activity on chymotrypsin ( Figure 5C) and trypsin ( Figure 5D). Similarly, the protease inhibitor from T. dicoccoides (WeCI) was shown to be stable in a wide pH range (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) 47 but, in contrast, the BmPI from B. monosperma was shown to maintain activity only in a pH range of 5-10. 43 The stability of LsCTI after heat treatment was remarkable; the molecule was able to maintain its inhibitory activity at all temperatures tested (37-100 ∘ C) ( Figure 5E), even when heated at 100 ∘ C for 180 min (Figure 5F), for both chymotrypsin and trypsin.…”
Section: Resultsmentioning
confidence: 99%
“…Mosquitoes transmit about 30 arboviruses of great importance to global public health, among which Aedes aegypti (Diptera: Culicidae), an anthropophilic mosquito, is widespread throughout the world and is the main vector of chikungunya, dengue and Zika viruses. Zika virus deserves special attention in view of its ability to cross the transplacental barrier and to lodge in the fetal nervous system, causing not only microcephaly, but also vision problems, deafness, arthrogryposis and dysphagia . Zika virus can also settle and survive in immunoprivileged tissues, such as the germ tissues present in the testicles, and thus Zika fever is a potential sexually transmitted infection .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain abnormalities and microcephaly are commonly reported (17,18) but CZS is also known to include arthrogryposis (reduced mobility of multiple joints due to contractures), dysphagia (difficulty swallowing), auditory deficits, visual impairment and other anomalies (19). Reports from the United States Zika Pregnancy Registry found that an estimated 5% (95% confidence interval [CI] = 4%-7%) of completed pregnancies with laboratory evidence of possible recent ZIKV infection (i.e., recent flavivirus exposure) had a fetus or infant with evidence of CZS.…”
Section: Introductionmentioning
confidence: 99%